Oridonin Attenuates Lipopolysaccharide-Induced ROS Accumulation and Inflammation in HK-2 Cells. (27th February 2020) - Huang, Jen-Hsuan; Lan, Chou-Chin; Hsu, Ya-Ting; Tsai, Cheng-Lin; Tzeng, I-Shiang; Wang, Po; Kuo, Chan-Yen; Hsieh, Po-Chun
Abstract : Renal tubulointerstitial inflammation plays an important role in chronic kidney disease (CKD). Inflammation reduction is a good strategy to combat CKD. Oridonin, an ent-kaurane diterpenoid isolated from Rabdosia rubescens (Donglingcao), is considered as an effective natural candidate for the treatment of anti-inflammatory, antiviral, and antibacterial activities, including liver fibrosis and many tumors; however, no study has demonstrated its effect on lipopolysaccharide- (LPS-) induced renal inflammation. To investigate the anti-inflammatory effects of oridonin on human renal proximal tubular epithelial cells (HK-2 cells), the expression levels of c-Jun N-terminal kinase (JNK) and reactive oxygen species (ROS) were evaluated by Western blot analysis and 2′, 7′-dichlorofluorescein diacetate (DCF-DA) staining, respectively. The level of intracellular ROS increased in a dose-dependent manner following LPS treatment, whereas oridonin inhibited this effect, suggestive of its ability to prevent ROS accumulation. As the mitogen-activated protein kinase (MAPK) family of enzymes plays an important role in physiological responses, we examined the activation of JNK by Western blotting and found that oridonin attenuated LPS-induced JNK phosphorylation. Oridonin also attenuated RAW 264.7 cell chemotaxis towards LPS-treated HK-2 cells. Taken together, oridonin protected against LPS-induced inflammation including ROS accumulation, JNK activation, NF- κ B nuclear translocation in HK-2 cells, and functionally blocked macrophage chemotaxis towards LPS-treated HK-2 cells. Oridonin may exhibit therapeutic potential by the anti-inflammation effect in LPS-treated HK-2 cells.